2011
DOI: 10.1093/ecam/neq045
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Attenuates Anxiety‐Like Behavior by Normalizing Amygdaloid Catecholamines during Ethanol Withdrawal in Rats

Abstract: Previously, we demonstrated acupuncture at acupoint HT7 (Shen-Men) attenuated ethanol withdrawal syndrome by normalizing the dopamine release in nucleus accumbens shell. In the present study, we investigated the effect of acupuncture on anxiety-like behavior in rats and its relevant mechanism by studying neuro-endocrine parameters during ethanol withdrawal. Rats were treated with 3 g kg−1day−1 of ethanol (20%, w/v) or saline by intraperitoneal injections for 28 days. The rats undergoing ethanol withdrawal exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 66 publications
4
30
0
Order By: Relevance
“…that the selective NEergic alpha1 receptor antagonist prazosin concurrently blocks the anxiety and the increase in ethanol intake induced by EW, reflecting the positive correlation between the NEergic system and the HPA in the regulation of ethanol consumption. The simultaneous hyperactivation of NE and CRF in the central nervous system during EW has also been demonstrated in our previous studies showing elevated activation in both amygdaloid NE and CRF during EW [8,9]. Additionally, in a recently published study, we also reported increased CRF protein expression in the rat PVN 24 hours after cessation of ethanol administration [12].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…that the selective NEergic alpha1 receptor antagonist prazosin concurrently blocks the anxiety and the increase in ethanol intake induced by EW, reflecting the positive correlation between the NEergic system and the HPA in the regulation of ethanol consumption. The simultaneous hyperactivation of NE and CRF in the central nervous system during EW has also been demonstrated in our previous studies showing elevated activation in both amygdaloid NE and CRF during EW [8,9]. Additionally, in a recently published study, we also reported increased CRF protein expression in the rat PVN 24 hours after cessation of ethanol administration [12].…”
Section: Discussionsupporting
confidence: 86%
“…Acute ethanol increases hypothalamic NE neosynthesis [4] and plasma corticosterone (CORT) secretion [5], and chronic ethanol can produce elevated blood glucocorticoid levels as well as increased activity in the sympathetic nervous system [6]. Dar and Wooles [7] have reported increased hypothalamic NE concentrations in EW mice, and we have also demonstrated that EW raises amygdaloid NE and CRF mRNA levels in rats [8,9].…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…, , Zhao et al . ). Several respondents in our study experienced that their ability to focus was sharpened, as well as their ability to deal with everyday issues.…”
Section: Discussionmentioning
confidence: 97%
“…Studies on rats reinforce this hypothesis (Zhao et al . ), suggesting acupuncture may lead to fewer symptoms of ethanol withdrawal (Lee et al . ).…”
Section: Introductionmentioning
confidence: 99%